2018
DOI: 10.2174/1874210601812011113
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Etiology and Antimicrobial Therapy of Peri-implantitis: A Comprehensive Review

Abstract: Introduction: Implants have turned out to be a well-established therapy in dental practice for the replacement of missing teeth and restoration of function. Peri-implant disease denotes the inflammatory condition of surrounding soft and hard tissues. Two terminologies are covered under the impression of peri-implant pathology; peri-implantitis and mucositis. Peri-implant mucositis is a reversible inflammatory process limited to soft tissues around an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…By eradicating subgingival microorganisms still present after traditional mechanical periodontal therapy, systemic periodontal antibiotic therapy seeks to supplement mechanical periodontal treatment and boost the host defense system in overcoming the infection. [ 29 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By eradicating subgingival microorganisms still present after traditional mechanical periodontal therapy, systemic periodontal antibiotic therapy seeks to supplement mechanical periodontal treatment and boost the host defense system in overcoming the infection. [ 29 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, navigating these new frontiers responsibly is crucial, ensuring rigorous research, evidence-based practice, and patient-centered care. With interdisciplinary collaboration, ethical considerations, and a commitment to advancing oral health, the future holds the potential for a paradigm shift in how oral diseases are approached and treated, ultimately leading to improved patient outcomes and a reimagined standard of care [28][29][30].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Bacterial infections are a common cause of endoosseous mini-implant failure. 15 Various studies have suggested reducing inflammation rates by taking daily mouthwash safely. 16 17 According to Nugraha et al, they concluded that Robusta Green Coffee Bean (RGCB) ethanol extract might be effective against periimplantitis bacteria in vitro , and chlorogenic acid in RGCB has antibacterial, anti-inflammatory, antioxidant, pro-osteogenic properties, and antibone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Peri-implantitis is a polymicrobial illness that is mixed and changeable but is dominated by gram-negative anaerobic bacteria. 9 Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), and Prevotella intermedia (Pi) were discovered to be more frequent in peri-implantitis than in peri-implant health. 10 Pg produces virulence factors like capsules, fimbriae, and proteases that aid colonization and the activation of dysbiotic inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%